2021
DOI: 10.48550/arxiv.2108.07483
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relative Calibration of Radial Velocity for LAMOST Medium Resolution Stellar Spectra

Jianping Xiong,
Bo Zhang,
Chao Liu
et al.

Abstract: The Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST) started medianresolution spectroscopic (MRS, R∼7500) survey since October 2018. The main scientific goals of MRS, including binary stars, pulsators, and other variable stars are launched with a time-domain spectroscopic survey.However, the systematic errors, including the bias induced from wavelength calibration and the systematic difference between different spectrographs have to be carefully considered during radial velocity measurement. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The RV measurement is a vital ingredient of this study since detecting significant RV variations relies on RV differences. We adopted the maximum likelihood method described in Xiong et al (2021) to measure the relative RVs. We briefly describe the procedures as follows.…”
Section: Rv Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RV measurement is a vital ingredient of this study since detecting significant RV variations relies on RV differences. We adopted the maximum likelihood method described in Xiong et al (2021) to measure the relative RVs. We briefly describe the procedures as follows.…”
Section: Rv Measurementsmentioning
confidence: 99%
“…This means that the influence of uncorrected RV on the derived binary fraction is little and can be ignored. We also compared the observed binary fraction based on the RVs from Zhang et al (2021) and Xiong et al (2021) and found that the difference between the observed binary fractions derived in the two ways is less than 1.5%. Therefore, we kept using the RV rel from Xiong et al (2021) in the following analysis.…”
Section: Rv Measurementsmentioning
confidence: 99%
See 1 more Smart Citation